Salivary 1,5-Anhydroglucitol and AGEs Are Associated with Postural Instability in Diabetic Foot Patients - Lorenzo Brognara; Mar Sempere-Bigorra; Omar Cauli (Medicina)
Background and Objectives: Gait and posture alterations are reported in patients with diabetic foot. We evaluated whether gait and postural parameters are associated with a well-known parameter, e.g., glycated hemoglobin levels in blood, and the salivary markers 1,5-anhydro-D-glucitol (1,5-AG) and Advanced Glycation End-Products (AGEs) measured in saliva samples. Materials and Methods: Gait and postural impairment was assessed using a wearable inertial sensor, and the evaluation of balance/gait and risk of fall was determined by the Tinetti Scale and Downton Index, respectively. Glycemic control was measured by glycated hemoglobin concentration and fasting glycemia. The salivary concentration of 1,5-AG and AGEs was measured using an enzyme-linked immunosorbent assay. Results: Eighty-five patients were evaluated, revealing significant associations (p < 0.05) between salivary 1,5-AG and sway path displacement along the medio-lateral axis (rho = 0.365, p = 0.017) and sway area (rho = 0.334, p = 0.031) during tandem position tests with eyes closed. Salivary AGEs were significantly associated with sway path displacement along the anterior–posterior axis (rho = 0.419, p = 0.004) and medio-lateral axis (rho = 0.436, p = 0.002) in the tests performed with eyes closed, feet close together, and foam pads, as well as with sway area (rho = 0.387, p = 0.007). The concentration of HbA1c was significantly correlated with sway path displacement along the anterior–posterior axis in the tests performed with eyes closed, feet close together, and foam pads (rho = 0.236, p = 0.043), as well as with sway area (rho = −0.236, p = 0.043). A significant difference was observed in the salivary AGE concentration between patients with previous ulcers versus those without (p = 0.035). By applying Bonferroni correction for multiple comparisons, the associations remained significant (p < 0.05) for AGE concentration in saliva and postural instability parameters. Conclusions: The results suggest a link between salivary glycemic control biomarkers, in particular AGEs and postural changes in patients with diabetic foot, indicating a new interesting filed for further studies on fall risk.